Deconstructing the Privileged Status of Religion over the Status of Belief as the Root of Discrimination towards Kejawen Community - Wasisto, Muhammad Adiz (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
The Kejawen community, recognized as a belief system rather than a formal religion, faces systemic discrimination in Indonesia. This distinction underpins the country's recognition of its political and legal status, thereby impeding the rights of Indigenous practitioners, including Kejawen followers. Several factors contribute to this systemic discrimination: the Western conception of religion, the dichotomy between religion and belief enshrined in Article 29 of the 1945 Indonesian Constitution, the narrow definition of religion by the Indonesian Department of Religion, the association of indigenous beliefs with communism post-1965, and the application of blasphemy laws aimed at